Fundamentos E Práticas Nas Ciências Da Saúde 2021
DOI: 10.35587/brj.ed.0001071
|View full text |Cite
|
Sign up to set email alerts
|

Os Efeitos Da Terapia Do Exercício No Tratamento Dos Indivíduos Com Sorologia Positiva Para O Vírus Da Imunodeficiência Humana: Revisão De Literatura

Abstract: O conteúdo dos livros e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores. Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Furthermore, strength exercises were responsible for increasing lean mass, weight gain and muscle strength. 3,7 Infection chronicity and bodily changes caused by ART often have an impact on the psychological aspects of this group. In view of this, regular physical activity plays an important role as it is closely associated with reducing levels of anxiety and depression in PLHIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, strength exercises were responsible for increasing lean mass, weight gain and muscle strength. 3,7 Infection chronicity and bodily changes caused by ART often have an impact on the psychological aspects of this group. In view of this, regular physical activity plays an important role as it is closely associated with reducing levels of anxiety and depression in PLHIV.…”
Section: Introductionmentioning
confidence: 99%
“…According to studies, a significant reduction in symptoms of moderate to severe depression was observed in PLHIV undergoing intervention through regular PE. 7,8 However, low adherence by PLHIV to interventions related to PAP still constitutes a challenge for improving physical health, mental health and well-being in this group of patients. It is estimated that 50.7% of HIV-positive individuals comply with the World Health Organization (WHO) recommendations, which indicates practicing at least 75 to 150 minutes of intense aerobic physical activity or 150-300 minutes of moderate physical activity.…”
Section: Introductionmentioning
confidence: 99%